eMagRes 2014
DOI: 10.1002/9780470034590.emrstm1362
|View full text |Cite
|
Sign up to set email alerts
|

Pure Shift NMR Spectroscopy

Abstract: Pure shift NMR spectroscopy, or broadband homonuclear decoupled NMR spectroscopy, produces NMR spectra that contain only chemical shift information. In a pure shift NMR spectrum the effects of J-coupling are hidden so that all multiplets are collapsed to singlets. Pure shift methods can deliver a significant improvement in resolution of NMR signals and greatly reduce signal overlap. Pure shift NMR can be achieved using direct or indirect acquisition; for direct acquisition, real-time-or interferogram-based FID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 39 publications
2
78
0
Order By: Relevance
“…As with the pulse sequence originally described by Köver and coworkers, a scaling factor, K, is built into the pulse sequence to upscale the size of the homonuclear 13 C– 13 C coupling constants being measured. Modifications inherent to the recently reported 1,1‐HD‐ADEQUATE and 1,n‐HD‐ADEQUATE experiments have also been incorporated, including an initial Testing for Adjacent Nuclei with a Gyration Operator (TANGO) cluster to efficiently dephase any residual 1 H– 13 C magnetizerion and a BIRD‐based ‘chunked’ data acquisition to achieve homodecoupling along the F 2 dimension …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with the pulse sequence originally described by Köver and coworkers, a scaling factor, K, is built into the pulse sequence to upscale the size of the homonuclear 13 C– 13 C coupling constants being measured. Modifications inherent to the recently reported 1,1‐HD‐ADEQUATE and 1,n‐HD‐ADEQUATE experiments have also been incorporated, including an initial Testing for Adjacent Nuclei with a Gyration Operator (TANGO) cluster to efficiently dephase any residual 1 H– 13 C magnetizerion and a BIRD‐based ‘chunked’ data acquisition to achieve homodecoupling along the F 2 dimension …”
Section: Resultsmentioning
confidence: 99%
“…As an example, NUS methods have thus been applied to facilitate better measurement of scalar and dipolar coupling constants . The development of broadband homodecoupled or pure shift NMR methods that collapse proton–proton couplings, thereby enhancing both resolution and sensitivity, has also been developed and is the subject of several recent reviews . Recently, we have communicated the development of homodecoupled analogs of the 1,1‐ADEQUATE and 1,n‐ADEQUATE experiments that, in a manner analogous to pure shift HSQC, can improve the sensitivity of these otherwise relatively low sensitivity but extremely useful experiments that can provide an alternative means of probing challenging structures when more sensitive methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[9] An extensive review of all these methods can be found in Refs. [1,2] In order to decouple one set of spins (active spins) from all their neighbours (passive spins), they have to be selected and manipulated independently of other spins. The first method that was published based on this idea was proposed in 1982 by Garbow et al, where active and passive spins are differently manipulated by using a bilinear rotation decoupling (BIRD) element ( Fig.…”
Section: Birth and Development Of A Great Ideamentioning
confidence: 99%
“…Recently developed pure shift analogs of the HSQC experiment have served to further increase resolution and sensitivity. [1012] In addition to 1 H and 13 C chemical shifts, HSQC spectra provide a wealth of structurally relevant information. In fact, there are successful examples of using just 1 H and multiplicityedited 1 H– 13 C HSQC data for automated structure verification purposes.…”
Section: Introductionmentioning
confidence: 99%